Margins of the negro and margins of society: when postmodern mobility is hindered by hegemonic chronology - Gonçalves, Davi Silva; Ávila, Eliana de Souza (Revista Língua&Literatura, 2013)
This article brings forward the discourse of hegemonic temporality and spatiality as challenged by Nael through his representation of the Amazon in Milton Hatoum’s novel The Brothers (2002). The transitory nature of postmodernism cannot be taken for granted since the mobility of marginalised regions like the Amazon is hindered by hegemonic notions of temporal and spatial linearity; such notions aim at imposing normative systems of behaviour whose agenda is to stop conceptual deviations from emerging. Therefore, deviating subjects are gradually forced to forsake both their present and past due to a future that never comes. Nevertheless, this investigation goal is to analyse if and how hegemonic chronology is unable to prevent the attitudes and positioning of The Brothers’ marginalised characters from historicising not only the possibility of existing in the future and in the past but, more importantly, in a queer and postcolonial present.